Corn Starch-Based Bionanocomposite Film Reinforced With ZnO Nanoparticles and Different Types of Plasticizers - Arifin, Heni Radiani; Djali, Mohamad; Nurhadi, Bambang; Azlin-Hasim, Shafrina; Masruchin, Nanang; Vania, P. Almira; Hilmi, Amani (Frontiers in Sustainable Food Systems, 2022)
Corn starch var. Paragon from Indonesia and carboxymethyl cellulose (CMC) was used to develop bionanocomposite film containing different types of plasticizers (glycerol (G) or sorbitol (S)) incorporated with zinc oxide (ZnO) nanoparticles (NPs) (0, 3, 5 wt.%) via casting method. The main objective of this study was to improve the properties of the bionanocomposite film with incorporated different types of plasticizers and ZnO NPs. The physicochemical properties of the film were systematically characterized. The results showed that the incorporation of sorbitol could significantly enhance the value of tensile strength, elongation, and Young's modulus than glycerol. In general, a higher concentration of ZnO NPs in the film could increase the tensile strength, reduce the water vapor permeability, decrease the water solubility, and influence the morphology, crystallinity, functional groups, and thermal stability of the films. The data showed that corn starch bionanocomposite film containing sorbitol with 5 wt.% ZnO NPs was the most optimal film as compared to other formulations as the solubility and water vapor transmission rate (WVTR) value significantly reduced, as well as increased the value of tensile strength, elongation, and Young's modulus. It can be concluded that the incorporation of glycerol or sorbitol plasticizers reinforced by ZnO NPs plays an important role in improving the properties of bionanocomposite film, hence the film has the potency to be used as sustainable and environmental friendly packaging.